Online Learning in Pandemic Covid-19: Difficulties Faced by the Students of Universitas Lancang Kuning - Refika Andriani; Syaifullah Syaifullah; Destina Kasriyati (Universitas Lancang Kuning, 2021)
This research aimed at describing the difficulties in online learning faced by the students during the first semester of Academic Year 2020/2021. The method of the research was descriptive quantitative by using online questionnaire with four indicators of learning obstacles for collecting the data. The sample of the research was 35 students of English Education Department of Faculty of Education and Teachers’ Training of Universitas Lancang Kuning. After analyzing the data by using descriptive statistics, it is found that the major difficulty is about the students’ physical constraints indicator. The score was about M=3.11 with “moderate” level. Then, non-social environment indicator was about M=2.57 with “moderate” level. The next difficulty was facility. The mean score was about 2.8 with “moderate” level. The next difficulty was from the educator. The mean score was about 2.13 with “moderate” level. The last difficulty was the students’ psychological constraints. The mean score was about 2.07 with “moderate” level. In conclusion, online learning is better implemented in well preparation. It needs all the elements’ readiness such as students, educators, institution, and also the government. It must include the mental and physical readiness. For organizing the online learning, both students and educator should be supported by facility such as qualified laptop or gadget and also fast internet connection. Besides that, lecturer should have qualified competence in organizing the online class so the students motivate in following the class. The last is about the environment. Having well and comfortable environment basically increases the students and lecturer motivation in conducting the online class.